On The Investıgatıon Of Speech Acts - Qarayeva, Gunay Qara (Advances in Social Sciences Research Journal, 2018)
The speech act is considered to be one of the important and complex sources of communication. The importance of speech act has already been accepted and has attracted the attention of linguists as an investigation object. The speech act can be considered multicomponental. The article deals with the investigation of speech acts. It also investigates the performatives in speech acts. The speech act is considered to be an important and comlex communication source. The identity of performative sentences in speech acts is discussed in the article. The article writes that the performative sentences express declaration, announcement, description, confirmation, prediction, etc. Performatives are accompanied by the performance of speech act. The article states that L.Wittgenstein introduces speech acts as “language games” and it is widely discussed in the article. The opinions of Wittgenstein L. and Austin J.about speech acts are discussed in the article as well.